Experimental study on pressure impact and vibration of long-distance coal slime transportation pipeline - LYU Fuyan; JIA Xuankai; LIU Yayun; XIA Zhengmeng; HAO Xuedi; WU Miao (Gong-kuang zidonghua, 2015)
Pressure and vibration signals of pump outlet of long-distance coal slime transportation pipeline were tested in industrial field, so as to determine reversing of S type pipe valve is direct cause of pipeline pressure impact and vibration. Conclusions were gotten through further analysis of pressure and vibration signals before and after reversing of the S type pipe valve by changing pumping output. Intensity of pipeline pressure impact and vibration increases with pumping output and axial vibration intensity is greater than radial vibration intensity when the pumping output is less than 75%. And the smaller the pumping output, the more intense the axial vibration compared to the radial vibration. Pressure impact and vibration of pipeline is less affected by the pumping output variation when the pumping output exceeds 75%.